Hospital-based antibiotic use in patients with Mycobacterium avium complex - Emily E. Ricotta; Kenneth N. Olivier; Yi Ling Lai; D. Rebecca Prevots; Jennifer Adjemian (ERJ Open Research, 2018)
Treatment guidelines exist for pulmonary Mycobacterium avium complex (MAC) infection, although studies suggest poor concordance in clinician practice. Using a national database including hospital encounters of laboratory-confirmed MAC patients, we sought to characterise US treatment practices. We assessed patients in the Premier Healthcare Database from 2009 to 2013 with two or more MAC-positive cultures or one MAC-positive culture and the International Classification of Diseases (9th revision) code for pulmonary nontuberculous mycobacteria (PNTM). Treatment was characterised by patient-, provider- and facility-level factors; significant differences were assessed (p<0.05). Multilevel Poisson regression estimated adjusted relative risks (aRR) of receiving guidelines-based or macrolide resistance-promoting regimens. Of 1326 MAC patients, 645 (49%) received treatment: 10% received guidelines-based treatment and 18% resistance-associated therapy. Patients were more likely to receive guidelines-based therapy if they had multiple hospital encounters (aRR 1.5), codes for PNTM (aRR 5.7) or tuberculosis (aRR 4.5) or radiological procedures (aRR 10.9); multiple hospital encounters (aRR 0.8) or a tuberculosis code (aRR 0.1) were less likely to be associated with receiving resistance-promoting regimens. In hospital-based MAC patients, half received antibiotics active against MAC, a low proportion received therapy based on MAC guidelines and many received antibiotics that promote macrolide resistance. Improved implementation of guidelines-based treatment is needed to decrease use of regimens associated with macrolide resistance.